A dual synergistic effect of titanium and curcumin co-embedded on extracellular matrix hydrogels of decellularized bone: Potential application in osteoblastic differentiation of adipose-derived mesenchymal stem cells. Issue 3 (11th February 2023) - Amirazad, Halimeh; Baradar Khoshfetrat, Ali; Zarghami, Nosratollah
Abstract: This research aims to design and fabricate a novel hydrogel-based composite as a functional biomimetic and biocompatible scaffold for amended osteoblastic differentiation of adipose-derived mesenchymal stem cells (ADMSCs). The extracellular matrix (ECM) hydrogel is an ideal scaffold in tissue engineering in terms of its structure mimics natural tissue. In this study, the fresh bovine femur was demineralized and decellularized; next, ECM hydrogel was obtained by digesting these matrices. Then, TiO2 and curcumin-loaded hydrogel (Hy/Ti/Cur) was fabricated besides TiO2 -loaded hydrogel (Hy/Ti) and curcumin-loaded hydrogel (Hy/Cur). Comparing the scanning electron microscopy (SEM) images of the pure network hydrogel and the rough morphology of Hy/Ti/Cur revealed that curcumin and titanium dioxide were successfully loaded into the hydrogel. In addition, FTIR spectroscopy and X-ray diffraction (XRD) validated these findings. The findings of the hydrogels' swelling test indicated the favourable impact of curcumin and titanium dioxide in hydrogels, which enhances water absorption capacity. Our results showed that the hydrogels were cytocompatible, and the cell viability on the hydrogels was elevated compared to the control. The synergistic effect of TiO2 and Cur co-embedded on ECM hydrogel (Hy/Ti/Cur) stimulates bone differentiation markers, such as Runt-related transcription factor 2 (RUNX-2) and osteocalcin (OCN) in ADMSCs cultured in normal and osteogenic medium. Moreover, Alkaline Phosphatase (ALP) activity and calcium deposition of ADMSCs cultured on engineered hydrogels were increased. These experiments showed that newly fabricated hydrogel has the potential to induce osteogenesis, which is recommended as an attractive scaffold in bone tissue engineering.